An analysis of the communication skills of coaches according to the perception of athletes who participated in intercollegiate football competition - Sunay, H.; Cengiz, R.; Yasar, O. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Football clubs are a part of system of communication and interaction. The qualification of the athletes are parallel with the trainers qualification. According to this fact, it is very important that trainers to improve their communication skills which are basics of learning and teaching process. The purpose of the study is determined to communication skills of trainers according to athletes perspective who have participated intercollegiate football tournament. Methods: The sampling of the study is made of 117 football players who are attended to intercollegiate football tournament during 30 April-4 May 2013. In investigation random sampling method was used. During the study basic personal information form was utilized. In addition to this Trainer communication skill survey` which was developed by Y+lmaz (2008). The Levene test was used to figure out normalization of data. During the analyze of data independent T test and one way Anova test were used besides descriptive statistical techniques. SPSS 16.0 statistic program were used to analyze to data. Results: According to study there were no significant differences between trainers communication skills and training age, position on field, educational department of football players. However, football players thoughts towards trainers communication skills are that their skills are effective but need improvement. Discussion: In the study of Ylmaz, et.al. which was researched on 739 athletes showed that individual sport trainers have more effective communication skills than team sports trainers. But also team sports trainers have sufficient communication skills however they need to work on their communication skills. Bayrak and Nacar studied on 209 athletes and they investigated trainers communication skills and results were that trainers mostly have adequately communication skills. According to Chih-Ming Yu (2016) in the organizations which have positive organizational climate, effects the communication skills of trainers. In contrary trainers should spend more time to develop on their communications skills.